DETERMINING THE VIABILITY OF WATERMELON EXOCARP AS A FEEDSTOCK FOR ETHANOL PRODUCTION. Issue 1 (2021) - Biose, O.; Imhontu, M.; Akenzua, O.; Ehigiamusoe, O.; Atsegha, B.; Onabe, J.; Daudeigha, J. Angalapu; Okorie, C.; Igbinomwanhia, D. Iyeke
No abstract available